2007
DOI: 10.1021/jp0665224
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the High Thermal Stability of Alkylidene Groups on the Surface of β-Mo2C

Abstract: Surface alkylidenes can be formed on β-Mo 2 C through the selective carbonyl bond scission of ketones and aldehydes. Spectroscopic studies show that alkylidene groups remain intact on the carbide surface to above 900 K under ultrahigh vacuum conditions. A rationalization for the anomalously high thermal stability is presented on the basis of surface analysis studies. It is shown that the relatively high reactivity of the clean carbide surface permits both carbonyl bond scission and other less selective process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…Hence, we rule out 2methylfuran desorption as being a significant process in the present system. In summary, we tentatively attribute the XPS signal to a mixture of h 2 (C,O) states (Figure 1b), surface alkylidenes (Figure 1c), and hydrocarbon fragments resulting from more extensive decomposition, as previously reported for cyclic ketones on bulk b-Mo 2 C by Oudghiri-Hassani et al [37] High-resolution XPS studies and reflectance absorbance infrared spectroscopy experiments are needed to describe the complex furfural/2D-a-Mo 2 C/Cu system with more molecular detail.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Hence, we rule out 2methylfuran desorption as being a significant process in the present system. In summary, we tentatively attribute the XPS signal to a mixture of h 2 (C,O) states (Figure 1b), surface alkylidenes (Figure 1c), and hydrocarbon fragments resulting from more extensive decomposition, as previously reported for cyclic ketones on bulk b-Mo 2 C by Oudghiri-Hassani et al [37] High-resolution XPS studies and reflectance absorbance infrared spectroscopy experiments are needed to describe the complex furfural/2D-a-Mo 2 C/Cu system with more molecular detail.…”
Section: Resultssupporting
confidence: 81%
“…The spectrum of the as-received sample displays a weak peak at 283.2 eV and a strong broad peak centered at 285.0 eV. The low binding energy peak is readily attributed to the carbide by reference to previous work from our group, [36,37] and data reported by Bauer et al and Gleichweit et al [38,39] Our previous studies found that b-Mo 2 C is characterized by a C(1s) binding energy of 282.8 eV and that b-Mo 2 C bearing excess C on the surface (prepared by exposure at 600 K to a small dose of propene) displays a binding energy of 283.2 eV. Bauer et al and Gleichweit et al reported that monolayer carbide on Mo(110) formed at 1200 K by exposure to C 2 H 4 displays a binding energy of 283.8 eV, while bulk carbide prepared by high exposures to ethylene shows a binding energy of 283.0 eV.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…This is consistent with the deposition of carbon and C x H y fragments on the carbide surface through the progressive decomposition of the alkylidene species. 19,32 However, a fraction of the propylidiene surface groups remain stable to 900 K consistent with previous reports of the anomalously high thermal stability of alkylidenes on the molybdenum carbide surface. 11,19,32 Complete removal of the alkylidenes from the surface occurs at 920 K as shown by the recombinative desorption peak shown in Fig.…”
Section: Surface Propylidienesupporting
confidence: 89%